Genetic predisposition to nephropathy and associated cardiovascular disease in people with type 1 diabetes: role of the angiotensinI-converting enzyme (ACE), and beyond; a narrative review - Kamel Mohammedi; Michel Marre; François Alhenc-Gelas (Cardiovascular Diabetology)
Abstract Hypertension, cardiovascular disease and kidney failure are associated with persistent hyperglycaemia and the subsequent development of nephropathy in people with diabetes. Diabetic nephropathy is associated with widespread vascular disease affecting both the kidney and the heart from an early stage. However, the risk of diabetic nephropathy in people with type 1 diabetes is strongly genetically determined, as documented in familial transmission studies. The search for the underlying genes has been extensive, using specific hypotheses, sibling linkage studies and genome-wide association studies (GWAS). The role of the angiotensinI-converting enzyme/kininase II (ACE) gene and genetic variability in ACE levels as a susceptibility and prognostic factor for diabetic nephropathy has been well documented in people with type 1 diabetes. The ACE gene insertion/deletion polymorphism, which is associated with plasma and tissue ACE levels, has been the most studied genomic variant in diabetic nephropathy. Recently, this polymorphism has also been associated with longevity in people with type 1 diabetes. The ACE I/D polymorphism has also been associated with vascular, extra-renal complications including myocardial infarction and lower-limb amputation in this population. Other genes and loci have been identified in linkage studies and GWAS, such as the COL4A3 gene or a region on chromosome 3q with the adiponectin gene. Replication was not always attempted and was rarely achieved, even for GWAS. Overall, effect sizes remain modest and no major gene has been identified, despite the strength of the genetic effect in transmission studies. We searched bibliographic databases for studies reporting genomic variants associated with diabetic nephropathy and meta-analyses of such studies. We selected important relevant studies for further discussion in this narrative review. This brief review attempts to summarise the current knowledge on the genetics of diabetic nephropathy and associated cardiovascular disease in people with type 1 diabetes, and discusses some conceptual and methodological issues relevant to the interpretation of past studies and the design of future ones. Graphical abstract Genetic determinism of diabetic nephropathy and associated cardiovascular disease in people with type 1 diabetes. Close-up on the AngiotensinI-Converting Enzyme gene. ACE, Angiotensin1-converting enzyme; I/D, ACE gene Insertion/Deletion Polymorphism; DN, diabetic nephropathy; CVD cardiovascular disease; ESKD, End-Stage Kidney Disease. ✔Genetically protected individuals